Review of the New World species of Pharaxonotha Reitter (Coleoptera: Languriidae) - Pakaluk, James (Revista de Biología Tropical, 1988)
The New World species of Pharaxonotha Reitter are reviewed. Four species are recognized: Pharaxonotha floridana (Casey) is known only from Florida, breeding in the cones of Zamia pumila; P. skirschii Reitter is a widespread, stored products pest, often associated with cotton bolls, stored grain, and edible tubers; two new species from Costa Rica, P. clarkorum and P. confusa, feed on the pollen of Zamia skinneri and Z. fairchildeana respectively. A key to the species found in the New World is presented.